The Relationship Between Level Of Religiosity And Family Support With Quality of Life of AMI Patients - Meilani, Lely; Faizin, Chamim; Noviasari, Nina Anggraeni (Universitas Muhammadiyah Yogyakarta, 2025)
Quality of Life (QoL) for acute myocardial infarction (AMI) patients is important. This study aims to analyze the religiosity and family support on the QoL for AMI patients. This study uses quantitative observational analytical methods with a cross-sectional design. Total sampling of data was collected by paying attention to the sample criteria at Roemani Hospital of the 74 respondents, inclusion was found to be 46 respondents. The study instrument used a Daily Spiritual Experience Scale (DSES) to religiosity level, Saragih family support questionnaire to assess family support as a variable independent. MacNew Health Related Quality of Life (HRQoL) to assess quality of life as a dependent variable. Analyzed data using tests rank Spearman. It was found that 80.43% of respondents had a high level of religiosity, 17.39% moderate, and 2.17% poor. There were 80.43% of respondents had good family support, and 19.57 % sufficient. Respondents had good QoL (78.26%), and poor (21.74%). These results showed that the religiosity level correlated with the QoL for AMI patients (p=0.000; r=+0.934). Family support correlated with the quality of life of AMI (p=0.000; r=+0.936). The higher religiosity level and family support, the higher the QoL for AMI patients. So, the patient must increase the level of religiosity and their families should be more supportive to improve QoL.